Well-designed manufacturing work improves some cognitive abilities in individuals with cognitive impairments - Banta Lavenex, Pamela; Blandin, Marie-Laure; Gaborieau, Caroline; Lavenex, Pierre (Frontiers in Rehabilitation Sciences, 2024)
Introduction Employment is recognized as a fundamental human right, which correlates with better physical and mental health. Importantly, well-designed work, which considers the physical, social, and psychological impacts of work, can serve to enhance the cognitive abilities of workers. Although often overlooked, work for individuals with disabilities, including cognitive impairments, is equally important for their physical and mental well-being. What has not been established, however, is whether well-designed work can also enhance the cognitive abilities of individuals with cognitive impairments. Methods Using a longitudinal study design, we investigated the impact of well-designed work on the cognitive abilities of 60 participants (operators) at the AMIPI Foundation factories, which employ individuals with cognitive impairments to produce electrical cables and harnesses for the automobile industry. The same operators were assessed at three different time points: upon hiring (n = 60), and after working in the factory for 1 year (n = 41, since 19 left the factory) and 2 years (n = 28, since 13 more left the factory). We used five cognitive tests evaluating: (1) finger and manual dexterity, bimanual dexterity, and procedural memory using the Purdue Pegboard; (2) sustained and selective attention using the Symbol Cancellation Task; (3) short- and long-term declarative verbal memory and long-term verbal recognition memory using Rey's Audio-Verbal Learning Test; (4) short- and long-term visual recognition memory using the Continuous Visual Memory Test; and (5) abstract reasoning using Raven's Standard Progressive Matrices. Results We observed improvements in procedural memory, sustained and selective attention, and short- and long-term visual recognition memory after working in the factory for 1 or 2 years. We did not observe improvements in finger or manual dexterity or bimanual dexterity, nor short- or long-term declarative verbal memory or verbal recognition memory, nor abstract reasoning. Discussion We conclude that, in addition to improving physical and mental well-being, well-designed manufacturing work can serve as a training intervention improving some types of cognitive functioning in individuals with cognitive impairments.